Pengenalan Penyakit Infeksi Jerawat, Gejala, Pencegahan dan Pengobatan pada Remaja - Nilda Lely; Masayu Azizah; Ade Arinia Rasyad; Agnes Rendowaty; Ema Ratna Sari; Erjon Erjon; Dewi Patmayuni; Lilik Pranata; Masayu Rosyidah (Lembaga Pengembangan Kinerja Dosen, 2025)
Acne is a skin disease caused by the bacteria Propionibacterium acnes, which infects the oil glands and pores of the skin. Hormonal changes that occur during puberty cause acne which is common in teenagers. With this problem, the community service team conducted education aimed at increasing the knowledge of teenagers to maintain their skin when acne occurs. The method of the activity was carried out with education with the material Introduction to Acne Infection Disease, Symptoms, Prevention and Treatment, the education participants were Elementary Madrasah and Junior High School students of the Ummul Quro Al-Hamidiyah Foundation totaling 50 students. The activity was carried out on Thursday, December 19, 2024. The results of the activity showed that the students were very enthusiastic about participating, and the students had understood what was explained by the speaker. The conclusion of the activity showed that there was an increase in student knowledge after being given education with the material on acne infection disease, symptoms, prevention and treatment in teenagers.